Existential philosophical idea of choice in education: implications for educational practices in Nigeria (2019)
This paper attempted an examination of the importance of choice in educational theory and practice. Using the philosophical method, the paper critically analysed the concept of choice in the existentialist philosophy with particular reference to the practice of education as well as the shortcomings of the school of thought. The paper established that a System of education based on the existentialist concept of choice will make learners realise that their choices make them creators of their own world; they will be able to engage in prior deliberations to make meaningful decisions, it will encourage the spirit of self-reliance through personal involvement in practices, and develop ability to apply critical thinking. It was suggested that in order to achieve liberal education, critical pedagogy should be employed by teachers as well as other agents of education to ensure that learners make informed and valuable choices in life